(3QSGdI aj GdJUhas
(3ChdgG (B:s
(3Qhi Yf Pi Gdfhf GdeUQi GdYGHO QMeg Gddg Ydjg bGd CLdSfi GdeJhcd Hjf jOjg hbGd di jG PG Gdfhf CfJ XQja GdRgGO hTjN GdYHGO s
(3BNQgG (B:s
(3bGd HcG CejQ GdeDefjf ef Pdc HcGA TOjOkG hJYLH ef Pdc hGddg Gdehab ddUhGH hEdjg GdeQLY hGdeBH hGdMeO ddg hMOg hGddg GdZfi hdG Mhd hdG bhI EdG HGddg GdYdi GdYXje hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg hSde JSdjekG cKjQkG OGFekG CHOkG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B(20981) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs